From Madrid to Zhejiang: Globalization, Educational Communities and Second Language Teaching - Pérez Milans, Miguel (Revista Complutense de Educación, 2010)
This paper focuses on how culture is socially constructed within the institutional logic of the school, in relation to different socio-political and economic processes linked to economic globalization in urban areas. The study comes from an ethnography carried out both in the contexts of Madrid (Spain) and Zhejiang (China). Taking critical sociolinguistic ethnography as theoretical/analytical framework, this paper uses interactional and ethnographic data in order to study what cultural resources are being produced, distributed and valued within both institutional spaces according their historical and socio-political conditions (that is, new immigration trends in Spain and the “open doors” economic reforms in China). Particularly, attention is paid to second language teaching practices, so that analysis focuses on what legitimated linguistic competence is constructed, reproduced and resisted in language classrooms.
Keywords: Education; Language ideologies; Globalization; Second language teaching practices; Classroom interaction; Language competence